Development of Cognitive and Psychomotor Task for EEG Application with Matlab-based GUI. Issue 1 (September 2020) - Sha'bani, MNAH; Fuad, N.; Jamal, Norezmi; Marwan, M.E.; Helmy Abd Wahab, Mohd; Zulkarnain Syed Idrus, Syed
Abstract: Conventionally, the evaluation of cognitive and psychomotor ability performance is typically based on self-writing reports. However, such assessment was unable to measure the actual performance during the task execution. Furthermore, the performance results perceived by the instructor is mainly subjective. For an alternative solution, a new approach is proposed to acquire brainwave signals (i.e. electroencephalogram (EEG)) during task performance. The application of EEG offers a promising approach in evaluating skill abilities at physiological level. Hence, a task related to the assessed skill needs to properly design to ensure the induced EEG signal is reliable for performance evaluation. With the aid of Graphical User Interface (GUI), the time frame of each response can be capture and recorded. Therefore, this paper presents the development of task assessment in evaluating the performance of cognitive and psychomotor abilities based on EEG signal.